The effect of hybrid coatings based on hydrogel, biopolymer and inorganic components on the corrosion behavior of titanium bone implants; Journal of Materials Chemistry B; Vol. 7, iss. 43 - Saveleva M. S. Mariia; Vladesku A. Alina; Kotrut M. K. Mikhay Kosmin; Van der M. L. Meeren Louis; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Parakhonskiy B. V. Bogdan; Skirtach A. G. Andre (2019, 2019)
Title screen